Silver(I)‐ and Base‐Mediated formal [4+3] Cycloaddition of in Situ generated 1, 2‐Diaza‐1, 3‐dienes with C, N‐Cyclic Azomethine Imines: An Efficient Protocol for the Synthesis of Tetrazepine Derivatives. Issue 13 (26th May 2020) - Li, Zefei; Li, Shuaikang; Kan, Tianjiao; Wang, Xinyue; Xin, Xin; Hou, Yunlei; Gong, Ping
Abstract: A silver(I)‐ and base‐mediated formal [4+3] cycloaddition reaction of in situ generated 1, 2‐diaza‐1, 3‐dienes with in situ formed C, N ‐cyclic azomethine imines has been developed. This protocol provided an efficient method for the synthesis of biologically important 1, 2, 4, 5‐tetrazepine derivatives with a wild substrate scope and excellent functional group tolerance in moderate to excellent yields. Abstract :